Assessment of host–guest molecular encapsulation of eugenol using β-cyclodextrin - Freitas, Camila Auad Beltrão de; Costa, Clauber Henrique Souza; da Costa, Kauê Santana; da Paz, Simone Patrícia Aranha; Silva, José Rogério A.; Alves, Cláudio Nahum; Lameira, Jerônimo (Frontiers in Chemistry, 2023)
Eugenol is a natural compound with a well-known repellent activity. However, its pharmaceutical and cosmetic applications are limited, since this compound is highly volatile and thermolabile. Nanoencapsulation provides protection, stability, conservation, and controlled release for several compounds. Here, eugenol was included in β-cyclodextrin and the complex was characterized through X-ray diffraction analysis (XRD) and Fourier-transform infrared spectroscopy (FTIR). Additionally, we used molecular dynamics simulations to explore the eugenol-β-cyclodextrin complex stability with temperature increases. Our computational result demonstrates details of the molecular interactions and conformational changes of the eugenol-β-cyclodextrin complex and explain its stability between temperatures 27-48 ºC.